De mijnwerkers van Geulle. Over de invloed van de mijnbouw op het Zuid-Limburgse platteland, 1900-1940 - Knotter, Ad (Studies over de sociaaleconomische geschiedenis van Limburg, 2024)
In this contribution I investigate the peasant-miners in the village of Geulle in the Dutch province of Limburg. In the first decades of the twentieth century the expanding coal mining industry in Limburg was increasingly able to recruit miners from the countryside, at first for the mines in and around the booming mining town of Heerlen in the eastern part, after 1925 also for the newly built state mine Maurits in the western part of South Limburg. The agricultural village of Geulle supplied miners from an early date. I am particularly interested in the first generations of miners in Geulle and to what extent they owned land and held on to some form of agricultural activity. With this research I hope to throw more light on the impact of the mining industry on the countryside of South Limburg in general.